Energy projects in isolated communities: How to develop an alternative for Garifuna ethnic groups in Honduras? - Centeno Sarmiento, Jorge Antonio; Casildo Álvarez, Reyna Samanta; Rodríguez, Rigoberto (LACCEI, 2025)
Will be studied weaknesses that express the inequity in the benefits pursued in the 2030 Sustainable Development Goals, especially Goal 7, which aims to guarantee access to clean and affordable energy, key to the development of communications, in addition to the objective 10, in order to reduce inequality that threatens the social and economic development of neglected communities. We will see that the socialization of energy projects in the Garifuna communities of Honduras presents serious challenges due to the lack of implementation of a process of prior, free and informed consultation, in accordance with the International labor organization (OIT) Convention 169, about indigenous and tribal peoples in independent countries, where the communities have been systematically excluded from decision making. The objective will be to find those obstacles that impact equitable insertion in the development of projects, such as the lack of political representation, distrust in consultation mechanisms, and general ignorance about the rights guaranteed by the Convention. Although some community members (32%) view energy projects with optimism, the majority perceive them with skepticism due to the lack of economic benefits, environmental impact, and violation of cultural and territorial rights. To overcome these challenges, it is essential to develop processes that guarantee prior, free and informed consultation, respecting the rights and forms of organization of the communities, recognizing the dignity of indigenous peoples and the cultural pluralism and solidarity of society, for decision-making.